Contemporary Christian-Muslim dialogue: two twenty-first century initiatives - Pratt, Douglas (Routledge studies in religion, 2021)
Introduction : Christian-Muslim dialogue -- Two 21st century dialogue initiatives -- The Building Bridges Seminar -- The Christian-Muslim Theological Forum -- Community : the people of God -- Scripture : word and witness of God -- Prophecy : proclaiming the word of God -- Prayer : communing with God -- Ethics : responsibility and justice -- Conclusion : signs and significance.